Isotope effects in aqueous solvation of simple halides - Videla, Pablo Ernesto (2018)
We present a path-integral-molecular-dynamics study of the thermodynamic stabilities of DOH⋯ X- and HOD⋯ X- (X = F, Cl, Br, I) coordination in aqueous solutions at ambient conditions. In agreement with experimental evidence, our results for the F- case reveal a clear stabilization of the latter motif, whereas, in the rest of the halogen series, the former articulation prevails. The DOH⋯ X- preference becomes more marked the larger the size of the ionic solute. A physical interpretation of these tendencies is provided in terms of an analysis of the global quantum kinetic energies of the light atoms and their geometrical decomposition. The stabilization of the alternative ionic coordination geometries is the result of a delicate balance arising from quantum spatial dispersions along parallel and perpendicular directions with respect to the relevant O-H⋯X- axis, as the strength of the water-halide H-bond varies. This interpretation is corroborated by a complementary analysis performed on the different spectroscopic signals of the corresponding IR spectra.